Aggregate, then Curate: Digital learning champions and informational resources - Whitworth, Andrew; Garnett, Fred (Proceedings of the International Conference on Networked Learning, 2012)
MOSI-ALONG is a project which investigates how formal and non-formal educational institutions can use social networking and media to help communities learn about, and thus nurture, online informational resources. It brings the curatorial and content creation expertise of a range of formal, informal and non-formal educational providers, which we term ‘digital learning champions’ (DLCs), to bear on processes of community inquiry. DLCs are engaged with through a range of offline and online media, helping communities develop resources that are relevant to their learning needs and interests. Community members judge the quality of their learning processes, and their use of technology, based on relevance, need, informal collaborative learning processes, individual skills and capacities. DLCs act as stewards (Wenger, White and Smith 2009) for the community’s resources, providing training, advice, content (pre-existing, or new), technologies and, ultimately, accreditation. We present the ‘Aggregate-then-Curate’ model as a 7-step framework for how learning processes can be networked, using social media and face-to-face techniques. The process can be entered or left at various points, and a range of media can come into play at each stage. There are many reasons why individuals or communities might be motivated to engage with the process, including the desire to solve problems in a community, learn skills, gain some kind of accreditation or funding, or just through personal interest. Community identities may even be formed through such work. Essentially then, the model is a description of how social media can enable the creation of community-defined, object-centred and good-quality collections of informational resources. The model could be picked up and used in other such connections between formal and informal learning processes, whether partners be community groups, museums, libraries, schools, universities or other digital learning champions.